Stem cell therapy for dogs with immune-mediated hemolytic anemia - Yeonmi Lee; Eunju Kang; Junguk Ju (Journal of Animal Reproduction and Biotechnology, 2024)
Three different dogs who had immune-mediated hemolytic anemia (IMHA) were treated for more than two weeks with blood transfusion in an animal clinic. Despite this treatment and hospitalization, there was no clinical improvement in clinical signs as well as complete blood cell count (CBC) including hematocrit (HCT) and C-reactive protein (CRP). All cases were then injected two or three times with allogeneic stem cells through an intravenous route for treatment. Upon administrating stem cells to the IMHA dogs, clinical conditions and the indexes of HCT and CRP were clinically improved within or close to normal ranges.